A Review on Medical Child Abuse and Child Protection - Ajlan Al-Jarshawi, Mustafa Hussein; Al-Imam, Ahmed (Journal of the Faculty of Medicine Baghdad, 2021)
Background Medical child abuse describes a child receiving unnecessary, harmful, or potentially harmful medical care at the caretaker’s instigation. Objectives To focus on medical child abuse as an entity and emphasize its epidemiology, clinical presentations, prevention, and management. Results In the UK, the annual incidence of medical child abuse in children below one year increased to 3:100,000, while its prevalence in Arabs, including Iraq, is ambiguous due to lack of evidence and improper clinician’s awareness. The mean age at diagnosis is 14 months to 2.7 years. Female caregivers are the most common offenders. Clinically, medical child abuse could fit into three stages; falsification of illness story, falsification of illness story and physical signs’ fabrication, or induction of illness in children. A successful diagnosis mandates a comprehensive review of medical records to identify discrepancies between caregivers’ stories versus clinical findings or investigations. Management requires recognizing abuse, halting it, securing the child’s safety, maintaining the family’s integrity when possible, and aborting unnecessary lateral referrals within the healthcare system. Conclusion Reported cases of medical child abuse are increasing steadily, while less severe ones go unrecognized. No diagnostic tool can help other than the physician’s high index of suspicion. The management follows the same principles applied for other forms of child abuse, while good medical practice ensures its prevention.